Prognostic importance of pulmonary artery measurement in patients with COVID-19 and correlation with computed tomography severity score (Annals of Medical Research, 2022)
Aim: To evaluate is the relationship of enlarged main pulmonary artery (mPA) diameter in COVID-19 with disease severity and early term prognosis by using computed tomography severity score (CTSS).Materials and Methods: 906 of 1650 COVID-19 patients with chest computed tomography (CT) included in the study. The patient groups were divided in two as short (≤7 day) and long (>7 day) hospitalization according to the length of hospital stay. The patients who were admitted to the intensive care unit (ICU) and those who died were also recorded. We assessed CTSS and PA diameter on CT images. Results: 540 (60%) patients had pneumonia. 291 (54%) of them were found to have pure ground glass opacity (GGO), 168 (31%) of them were found to have both GGO and consolidation, 60 (11%) of them were found to have consolidation and 21 (4%) of them were found to have crazy paving pattern. There was a significant correlation between PA diameter and hospitalization time (r:0.339; p
Keywords: COVID-19; chest CT; pulmonary artery